Eternity dress - Swinton, Tilda 1960-; Saillard, Olivier 1967- (Rizzoli, 2015)
"In Eternity Dress (2013), a garment is tailor-made in front of a live audience...A glorious ode to fashion, Impossible Wardrobes presents and elevates couture to a veritable art form." --
Keywords: Swinton, Tilda / Exhibitions; Fashion in art / Exhibitions; Performance art / Exhibitions; Clothing and dress in art / Exhibitions; Fashion / 21st century / Exhibitions; Ausstellungskatalog